DETECTION OF ANTIBODIES AGAINST BLUE TONGUE VIRUS IN YAKS (BOS GRUNNIENS) IN ISSYK KUL, FIRST REPORT - O. Avci; Y. Orhan; B. Oya; K. Mehmet; Y. Sibel; S. Atilla (Journal of Animal and Plant Sciences, 2018)
Bluetongue virus (BTV) caused infection is commonly determined in ruminants including sheep and cattle. However, there is a little information about the seroprevalence of BTV in yaks. The aim of this study was to describe the seroprevalence rate BTV in unvaccinated yaks in Issyk Kul, Kyrgyzstan. A total of 168 serum samples were collected from yaks between September to November 2012. Antibodies to BTV in sera were detected using a commercially available competitive enzyme-linked immunosorbent assay. 2.38% seroprevalence (n: 4) was determined in the samples as positive for BTV antibodies. This study indicates that antibodies against BTV are uncommon among the yaks in Issyk Kul. This is the first time that the seroprevalence of antibodies against BTV have been studied in yaks in Kyrgyztan. In conclusion; despite the low results large scale research is necessary for the prevention of BTV infection.
Keywords: BTV; ELISA; Yak; Antibody